Development of coordination qualities in cross-country skiers aged 13-14 years in the preparatory period of the annual macrocycle - Kotliar, S.; Toporkov, A. (Slobozhanskyi herald of science and sport, 2020)
Purpose: determine the influence of coordination qualities on the results of the special physical fitness of cross-country skiers aged 13-14 years in the preparatory period. Material and Methods: the study involved 30 athletes aged 13-14 years, whose experience of cross-country skiing 4-5 years, the qualification of athletes III - II category. The following methods are used in the work: analysis and generalization of scientific and methodological literature, pedagogical observation, pedagogical testing, pedagogical experiment. The methods of mathematical statistics to analyze the obtained data were used. Results: the use of special training for the development of coordination qualities young cross-country skiers led to improved results in overcoming the competitive distance in rollersking with a free style of 5000 m by 12.5%, at a distance of 100 m in a free style by 8.7% and a classic style on 8.5% (p<0.05). Conclusions: the use of exercises for the development of coordination qualities among 13-14 year old cross-country skiers and riders during the preparatory period made it possible to improve the results in rollersking with a classic and free style of movement.